Calcifying pseudoneoplasm of neuroaxis (CAPNON): a comprehensive immunohistochemical and morphological characterization of five cases - Soukup, Jiri; Kohout, Ales; Vosmikova, Hana; Hacova, Maria; Kaiser, Miroslav; Klener, Jan; Krejci, Tomas; Syrucek, Martin; Wozniakova, Maria; Gabalec, Filip; Cesak, Tomas (Virchows Archiv, 2022)
Calcifying pseudoneoplasm of neuroaxis (CAPNON) is a rare lesion of the central nervous system with uncertain histogenesis. We further explored phenotypic spectrum of the entity with respect to possible histogenesis. We collected 5 cases of CAPNONs, performed a detailed morphological assessment, and performed an extensive immunohistochemical analysis (EMA, progesterone receptors, MUC4, SSTR2A, cytokeratin AE1/3, cytokeratin 18, GFAP, neurofilaments, desmin, nestin, synaptophysin, S100 protein, SOX10, CD56, Podoplanin, SATB2, ERG, CD45, and CD163) to elucidate the histogenesis. Furthermore, we performed NGS analysis of one case. The clinical course was benign in all cases. All lesions showed extensively calcified matrix in multilobular arrangement, with a palisade of osteoblast-like cells. Characteristic fibrohyaline matrix was notable in 4/5 cases, while one case was myxoid with rod-like calcifications. Metaplastic lamellar bone was present in 4/5 cases and psammoma bodies were present in 2/5 cases. In 4/5 cases, areas of entrapped glial tissue were present. Expression of EMA was focally present in 3/5 cases, SSTR2A and nestin in 2/5 cases, and progesterone receptor in 2/5 cases in rare cells. We did not observe concomitant expression of EMA, SSTR2A, and progesterone receptor in the same cellular subsets. In one case, NGS showed multiple chromosomal alterations and missense mutation in PIK3CA, attributable to the admixed meningothelial population compatible with meningioma. In another case, biphasic proliferation with myoepithelial phenotype was present. The lesions showed no lineage-specific immunoprofile. Additional pathology was identified in two cases, furthermore suggestive of a possible reactive origin of the lesion.
Keywords: meningeom; Receptors, Progesterone; Meningioma; lidé; Meningeal Neoplasms; meningeální nádory; receptory progesteronu; Nestin; Calcinosis; Humans; kalcinóza; nestin